Case report: Right vertebral and carotid artery anomalies with an aberrant right subclavian artery in two patients - Chen, Jiang; Liu, LunXin; Kou, Xiaobo; Wang, Chaohua (Frontiers in Neurology, 2023)
Abnormal origins of the vertebral artery with supra-aortic vessel variants are exceedingly uncommon. Herein, we present two cases of the vertebral artery originating from the right common carotid artery associated with the right subclavian artery arising separately as the initial branch of the aortic arch, followed by the right common carotid artery. We reviewed the embryology of the anomalous origins of the vertebral and subclavian arteries. These variants can significantly affect surgical planning and cause severe clinical symptoms.